Clinical Evaluation of the Accuracy of the Panbio™ COVID-19/Flu A&B Rapid Panel: A Combination Antigen Rapid Diagnostic Test for the Omicron Variant and Influenza A Virus - Yamagishi, Hirokazu; Tamura, Daisuke; Yamazaki, Masahiko; Abe, Takashi; Mitamura, Keiko; Tajima, Toshihiro; Osaka, Hitoshi (Viral immunology, 2024)
It is difficult to differentiate between coronavirus disease 2019 (COVID-19) and influenza based on the symptoms. In the present study, a newly developed antigen rapid diagnostic test (Ag-RDT) called Panbio™ COVID-19/Flu A&B that can simultaneously detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A/B virus was evaluated. Its accuracy was evaluated using 235 pairs of nasopharyngeal samples collected from patients with respiratory symptoms and fever (>37.5°C). Reverse transcription polymerase chain reaction was used as a reference method to evaluate the accuracy of the SARS-CoV-2 detection. We confirmed the accuracy of the developed Ag-RDT against the Omicron variant where the sensitivity and specificity were 94.8% and 100%, respectively. In addition, to identify the influenza A virus, a noninferiority test was conducted using a commercial Ag-RDT, which has a sensitivity and specificity in comparison with viral culture of 94.8% and 98.4%, respectively. The positive and negative predictive values for influenza A virus were 98.5% and 98.1%, respectively, for the Panbio COVID-19/Flu A&B test. The evaluation of this newly developed Ag-RDT using clinical samples suggests that it has a high efficacy in clinical settings.